Non-Additive Transcriptional Profiles Underlie Dikaryotic Superiority in Pleurotus ostreatus Laccase Activity - Castanera, Raúl; Omarini, Alejandra; Santoyo, Francisco; Pérez, Gúmer; Pisabarro, Antonio G.; Ramírez, Lucía (PLOS ONE, 2013)
Background The basidiomycete Pleurotus ostreatus is an efficient producer of laccases, a group of enzymes appreciated for their use in multiple industrial processes. The aim of this study was to reveal the molecular basis of the superiority of laccase production by dikaryotic strains compared to their parental monokaryons. Methodology/Principal Findings We bred and studied a set of dikaryotic strains starting from a meiotic population of monokaryons. We then completely characterised the laccase allelic composition, the laccase gene expression and activity profiles in the dikaryotic strain N001, in two of its meiotic full-sib monokaryons and in the dikaryon formed from their mating. Conclusions/Significance Our results suggested that the dikaryotic superiority observed in laccase activity was due to non-additive transcriptional increases in lacc6 and lacc10 genes. Furthermore, the expression of these genes was divergent in glucose- vs. lignocellulose-supplemented media and was highly correlated to the detected extracellular laccase activity. Moreover, the expression profile of lacc2 in the dikaryotic strains was affected by its allelic composition, indicating a putative single locus heterozygous advantage.